2023
DOI: 10.5603/pjnns.a2023.0019
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in progressive supranuclear palsy syndrome (PSPS) and corticobasal syndrome (CBS)

Abstract: Introduction. Progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) are clinical manifestations of tauopathies. They are commonly associated with rapid motor and cognitive deterioration. Sleep disturbances are less frequently described as a feature of these diseases, though they are reported among 50-75% of PSP patients.State of the art. Apart from various clinical manifestations, sleep abnormalities in PSP and CBS seem to be a factor enhancing pathogenesis as well its consequences. Multiple res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The lack of influence of sleep disorders in PSP patients on the occurrence of ICDs may be due to a different type of sleep disorders and other mechanisms of their development compared to PD [69,70]. In PSP, which is a tauopathy, the most common sleep disorders are deviated sleep architecture and insomnia, and they are more severe than those occurring in PD, which is mainly associated with more severe neurodegenerative changes in the brain stem and greater severity of orexin neurotransmission disorders than PSP [71][72][73]. In PD, however, REM sleep disorders (RBD), which are typical for synucleinopathies, are more than twice as common, which some researchers associate with a higher incidence of ICDs [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of influence of sleep disorders in PSP patients on the occurrence of ICDs may be due to a different type of sleep disorders and other mechanisms of their development compared to PD [69,70]. In PSP, which is a tauopathy, the most common sleep disorders are deviated sleep architecture and insomnia, and they are more severe than those occurring in PD, which is mainly associated with more severe neurodegenerative changes in the brain stem and greater severity of orexin neurotransmission disorders than PSP [71][72][73]. In PD, however, REM sleep disorders (RBD), which are typical for synucleinopathies, are more than twice as common, which some researchers associate with a higher incidence of ICDs [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that in AD sleep may be affected by abnormalities in orexin regulations, which may be linked with tau and beta-amyloid secretion, accumulation and clearance [31]. Orexin is related with abnormalities in parkinsonisms, although it is not known whether the factor is one of the causes of, or rather a consequence of, the pathological pathways observed in the diseases [32,33]. In diseases affected by Lewy bodies such as PD or DLB, the pathology selectively affects the regions of the hypothalamus, among which can be mentioned orexin/ /hypocretin neurons, tuberomammillary nucleus and lateral tuberal nucleus [34,35].…”
Section: Orexin In Parkinsonismsmentioning
confidence: 99%
“…These findings include neurodegenerative biomarker research, longitudinal cohort outcome investigations, and pathological confirmation from both autopsy series and demonstration of extranigral α-synuclein pathology in living patients with RBD [ 16 ]. Furthermore, a recent review has highlighted that RBD, which has been primarily described in synucleinopathies, has also been found to be present in other atypical parkinsonisms such as progressive supranuclear palsy syndrome (PSPS) and corticobasal syndrome (CBS) [ 18 ]. Among RBD patients, it was observed that 74% of subjects met Movement Disorders Society criteria for a diagnosis of prodromal PD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%